Dasar Dan Prinsip Penerapan Ekonomi Islam Dalam Al-Qur’an - Ahmad Royhan Firdausy; Supriyadi (TAFAQQUH, 2023)
The basis and principles of economic application are the foundation or guideline that limits humans in carrying out economic activities. These limitations aim to ensure that economic functions in accordance with Islamic teachings can be applied. Because the purpose of the economy is to control human needs in carrying out their duties. The research method used in this paper is a descriptive analysis method, with a type of research on library materials (Library Research). The primary sources used as library material in this research are verses from the Al-Qur'an and hadiths relating to the basics and principles of applying Islamic economics in the Al-Qur'an. Including books, books or research results according to that theme. The basics of implementing Islamic economics as stated in the Qur'an are freedom to carry out economic activities (QS al-Baqarah [2]: 29), subjugation of the universe as a gift to humans (QS. Luqman [31]: 20, designation of humans as a manager of the universe (QS. al-An'am [6]: 165), orders to work (QS. Taubah [9]: 105), ideal concept in work (QS. Al-Qashash [28]: 73), and enjoy the results of work (QS. al-Mulk [67]: 15). The principles of implementing Islamic economics are the principle of consuming food of a halal and good type (QS. al-Baqarah [2]: 168), the principle of prohibiting consumption the result of false work (QS. al-Baqarah [2]: 188, the principle of prohibiting excesses in economic activity (QS. al-A'raaf [7]: 31), the principle of fulfilling one's mandate (QS. an-Nisa' [4]: 58), the principle of commitment in agreements (QS. al-Maidah [5]: 1) and the principle of honesty QS. al-A'raaf [7]: 85).